2015
DOI: 10.1371/journal.pone.0141646
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Waterborne Disease Outbreaks Associated with Small Non-Community Drinking Water Systems in Canada and the United States

Abstract: BackgroundReports of outbreaks in Canada and the United States (U.S.) indicate that approximately 50% of all waterborne diseases occur in small non-community drinking water systems (SDWSs). Summarizing these investigations to identify the factors and conditions contributing to outbreaks is needed in order to help prevent future outbreaks.ObjectivesThe objectives of this study were to: 1) identify published reports of waterborne disease outbreaks involving SDWSs in Canada and the U.S. since 1970; 2) summarize r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 47 publications
3
47
0
Order By: Relevance
“…Pons et al (2015) reported that having no treatment system is one of the leading causes of outbreaks in SDWSs. Edwards et al (2012) examined the safe operation characteristics of small commercial water systems in British Columbia, Canada, and concluded that the lack of a treatment system and water source vulnerability are among factors causing adverse conditions in SDWSs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pons et al (2015) reported that having no treatment system is one of the leading causes of outbreaks in SDWSs. Edwards et al (2012) examined the safe operation characteristics of small commercial water systems in British Columbia, Canada, and concluded that the lack of a treatment system and water source vulnerability are among factors causing adverse conditions in SDWSs.…”
Section: Discussionmentioning
confidence: 99%
“…In simple terms, drinking water is considered safe when it does not contain pathogens or unsafe concentrations of toxic chemicals or radioactive substances (MOE, 2006). Although approximately 15% of Canadians use Small Non-Community Drinking Water Systems (SDWSs), more than 50% of the waterborne outbreaks in Canada are associated with these systems (Pons et al, 2015). This study aims to examine the SDWS operational characteristics and their relationships with Adverse Water Quality Incidents (AWQIs).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From a total of 1,995 citations, we identified 50 relevant articles reporting 293 unique outbreaks. Failure of an existing water treatment system (22.7%) and lack of water treatment (20.2%) were the leading causes of waterborne outbreaks in SDWSs [2].…”
Section: Introductionmentioning
confidence: 99%
“…Disease burden from unsafe water, sanitation and hygiene (WSH) accounts for 5.3% of all deaths and 6.8% of all DALYS all over the world (Pruss- Ustam et al, 2002). Despite wealthy economies and access to proven drinking water-treatment technologies, significant outbreaks of waterborne intestinal diseases have also occurred in developed countries of North America and Western Europe over the last 10-15 years (Pons et al, 2015). In 2011, around 768 million people relied on unsatisfactory water supply having high levels of pathogen contamination (WHO and UNICEF, 2013).…”
mentioning
confidence: 99%